Initial Formative Assessment for the Implementation of P5 with a Local Wisdom Theme - Dyah Febria Wardhani; Deasy Arisanty; Agung Nugroho; Umi Baroroh Lili Utami (JPG (Jurnal Pendidikan Geografi), 2025)
The Merdeka Curriculum in Indonesia introduces flexible learning through the Projek Penguatan Profil Pelajar Pancasila (P5), yet its implementation faces challenges, including low student readiness and varying teacher perceptions. The success of this program depends on teachers' understanding, the application of 4C skills (critical thinking, collaboration, communication, and creativity), and the integration of technology. Local wisdom is also a crucial element, as it serves as a resource for character development and cultural identity, fostering more meaningful and relevant learning. An ethnoscience approach, which connects local wisdom with scientific concepts, further contributes to a more contextual and inclusive learning environment. This study aims to examine how early formative assessment can strengthen student readiness for local wisdom-based P5 projects by identifying their needs and potential before the learning process begins. A mixed-methods approach was used to analyze data from seventh- and eighth-grade students at SMPN 1 Paramasan. The findings revealed a need to reinforce students' understanding of the local Dayak Paramasan tribe, as well as their critical thinking and collaboration skills. The results underscore the importance of a structured instructional approach to optimize P5 implementation and ensure students' success.